Myasthenia Gravis Pada Wanita 42 Tahun: Laporan Kasus - Tania Tamara; Fitriyani (Medula, 2024)
Myasthenia gravis (MG) is an autoimmune disease, MG attacks the postsynaptic membrane, disrupts neuromuscular transmission, and causes skeletal muscle weakness and fatigue. Myasthenia gravis is a treatable disease but can result in significant morbidity and even death. This article aims to discuss the diagnosis, therapy, and prevention of disease progression. A 42-year-old woman presented with complaints of weakness all over the body since 4 years ago, which has worsened in the last 2 months, accompanied by shortness of breath, coughing, difficulty speaking, and a nasal voice. Physical examination revealed ptosis (+/+), motor strength 3/3/3 / 3/3/3. Laboratory examination showed leukocytes 11,500/µL. Electromyography (EMG) and nerve conduction velocity (NCV) examination showed a 10% reduction in repetitive nerve stimulation (RNS), Harvey Maslan (+). The clinical symptoms of MG are fluctuating weakness in the extra-ocular, bulbar, and proximal muscles. Signs of muscle weakness include unilateral or bilateral ptosis, binocular diplopia, inability to lift the head straight, dysphagia, and dysarthria. MG can progress generally to proximal muscle weakness with varying degrees of severity. The main treatments for MG are cholinesterase enzyme inhibitors and immunosuppressive agents. Previously, a case of myasthenia gravis was described in a 42-year-old female patient. The diagnosis of this case was made based on a previous history of myasthenia gravis, symptoms of weakness in the ocular, bulbar, and extremity muscles. A possible risk factor for re-triggering MG symptoms in patients is infection. Establishing the current diagnosis and treatment options for MG play an important role in preventing worse disease progression.